Psychiatric patients' perception of physical restraint. (16th October 2015) - Fugger, G.; Gleiss, A.; Baldinger, P.; Strnad, A.; Kasper, S.; Frey, R.
Abstract : Objective: To investigate psychiatric patients' subjective perception during and after belt fixation. Method: All patients who were involuntarily admitted and physically restrained at a psychiatric intensive care unit within an 18‐month study period were analysed. Ratings were obtained at four visits when questioning was possible. Results: Within a heterogeneous diagnostic sample of 47 patients, only 12 patients were eligible to participate during belt fixation. After cessation of fixation, eight patients lacked any memory of restraint, while 36 could be questioned. Visual analogue scale median scores indicated powerlessness and depressiveness rather than anxiety and aggression. Patients' acceptance of the coercive measure was significantly higher ( P = 0.003), while patients' memory was significantly lower than expected ( P < 0.001). About 50% of the patients documented high perceived coercion, and post‐traumatic stress disorder (PTSD) could be supposed in a quarter of the restrained individuals. Subjective perceptions concerning fixation showed no significant changes over time. Results showed high interindividual variability. Conclusion: Visual analogue scale revealed that belt fixation seemed to be forgotten or accepted in the majority of patients, probably due to psychiatric intensive care, psychopharmacological treatment and clinical improvements. The responses of a quarter of the patients assessed before discharge may be in accordance with symptoms of PTSD.